2020
DOI: 10.1093/eurheartj/ehaa841
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic clustering of dilated cardiomyopathy patients highlights important pathophysiological differences

Abstract: Aims The dilated cardiomyopathy (DCM) phenotype is the result of combined genetic and acquired triggers. Until now, clinical decision-making in DCM has mainly been based on ejection fraction (EF) and NYHA classification, not considering the DCM heterogenicity. The present study aimed to identify patient subgroups by phenotypic clustering integrating aetiologies, comorbidities, and cardiac function along cardiac transcript levels, to unveil pathophysiological differences between DCM subgroups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 26 publications
4
60
0
Order By: Relevance
“…The use of artificial intelligence is evolving, predominantly in adult studies, using 'bigdata' and unsupervised ML approaches to classify phenotypes who may be treated similarly, with a predictable response. 25 Unbiased or unsupervised hierarchical clustering has been used to identify new phenotypes in cohorts of adults with heart failure. 26,27 Our approach could foreseeably be utilized in the same way in the phenotypically heterogenous paediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…The use of artificial intelligence is evolving, predominantly in adult studies, using 'bigdata' and unsupervised ML approaches to classify phenotypes who may be treated similarly, with a predictable response. 25 Unbiased or unsupervised hierarchical clustering has been used to identify new phenotypes in cohorts of adults with heart failure. 26,27 Our approach could foreseeably be utilized in the same way in the phenotypically heterogenous paediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…68 Contributing factors to PPCM include genetic predisposition 69 as well as auto-immune responses. [70][71][72] Using such factors, all be it indirectly, to define phenoclusters 73 -it could be possible to identify novel therapeutic targets to guide personalized medicine in PPCM.…”
Section: Peri-partum Cardiomyopathymentioning
confidence: 99%
“…Unsupervised clustering algorithms may also be able to help our understanding of phenotypic heterogeneity in DCM, as they can identify pathophysiologically similar individuals who may respond in a uniform and predictable way to treatment [ 100 ]. Indeed, a recent study identified four different DCM phenotype subgroups (“phenogroups”) using an unsupervised hierarchical clustering algorithm, which was validated in two external registries: the Italian Trieste Registry and a cohort from Madrid [ 4 , 101 , 102 ]. The four identified phenogroups were summarised as (i) mild systolic dysfunction, (ii) auto-immune disease, (iii) arrhythmic, and (iv) severe systolic dysfunction.…”
Section: Big Data Research Opportunities and Artificial Intelligenmentioning
confidence: 99%
“…The four identified phenogroups were summarised as (i) mild systolic dysfunction, (ii) auto-immune disease, (iii) arrhythmic, and (iv) severe systolic dysfunction. The latter three groups had comparable and relatively unfavourable outcome compared to the first phenogroup [ 101 ]. Whether these subgroups can be used to guide clinical decision-making remains to be investigated [ 5 ].…”
Section: Big Data Research Opportunities and Artificial Intelligenmentioning
confidence: 99%